Bioconcentration Factor of Copper (Cu), Lead (Pb), and Zinc (Zn) in Anadara indica Related to the Water Quality in Coastal Areas - Takarina, Noverita Dian; Bengen, Dietriech Geoffrey; Sanusi, Harpasis Slamet; Riani, Etty (UI Scholars Hub, 2013)
The Garapan river mouth forms part of the Tanjung Pasir coastal area. This region receives materials not only from coastal waters but also from domestic sewage and industrial wastewater that contains heavy metals such as Cu, Pb, and Zn. On the contrary, the Cibungur river mouth in the different coastal area, receives relatively lower amounts of domestic sewage and industrial wastewater. The objective of this study was to determine the Cu, Pb, and Zn content in the coastal sediment as well as the levels of A.indica and their relationship with water quality parameters. Samples were collected from four stations located in the Garapan and Cibungur river mouths and were analyzed for metal content using atomic absorption spectrometry Shimadzu 6300. Samples of A. indica found in the field are categorized into three diferent size classes. It is because size related to heavy metal accumulation. Results showed that bioconcentration factor (BCF) values were Zn>Cu>Pb in both locations. Small size A. indica tends to have higher values of BCF for Cu and Zn compared to medium and larger sized samples. Furthermore, the BCF values of Cu, Pb, and Zn in A. indica were higher when the sediment had a lower concentration of organic matter.